Pengaruh Penambahan Bubuk Kulit Biji Kakao (Theobroma cacao L.) Terhadap Sifat Fisikokimia Dan Organoleptik Brownies Crispy - Permana, I Dewa Gde Mayun; Mutyasih, Komang Jyoti; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Brownies crispy are chocolate cakes that have a crunchy texture so they are quite popular as a snack, but based on the formulation brownies crispy have a fairly low fiber content. The addition of cocoa bean husk powder to crispy brownies can increase the fiber content of the product. This study aims to determine the effect of adding the right cocoa bean husk powder (Theobroma cacao L.) to produce brownies crispy with the best physicochemical and organoleptic properties. The design used in this study was a Completely Randomized Design consisting 6 concentration levels of cocoa bean husk powder, namely: 0%, 5%, 10%, 15%, 20%, and 25% with three replications. Parameters tested were water content, crude fiber content, antioxidant activity, texture (hardness), color intensity (L, a*, and b*), and hedonic sensory evaluation (color, aroma, texture, taste, and overall acceptability). The data were analyzed using variance and if the treatment had a significant effect then it was continued with the Duncan Multiple Range Test (DMRT) at 5% level using Statistical Product and Service Solution (SPSS). The results showed that the concentration of cocoa bean husk powder had a significant effect on water content, crude fiber content, antioxidant activity, hardness texture profile, color intensity (L, a*, and b*) and had no significant effect on hedonic sensory analysis on parameters of color, aroma, texture, taste, and overall acceptability. The best characteristics of brownies crispy was the addition of 25% cocoa bean husk powder with a moisture content value of 1.38%, 4.15% crude fiber content, 48.38% antioxidant activity, 32 hardness texture profile 32,24 N, color intensity L 23.03, a* 9.20, b* 14.20, and sensory acceptability was liked.